2016
DOI: 10.1515/tjb-2016-0197
|View full text |Cite
|
Sign up to set email alerts
|

Approach to pre-analytical errors in a public health laboratory

Abstract: Background and objective:We aimed to investigate the effect of “training about the pre-analytical phase” and “technological arrangements in laboratory information systems (LISs) and tube barcoding system”, on decreasing PEs.Materials and methods:PEs in 2013 and 2014 were obtained from the LIS retrospectively in order to evaluate the effect of improvements. Ten quality indicators (QIs) described for pre-analytical phase were calculated. We compared QIs of the “improved year” with the past year. Four quality spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Furthermore, the accuracy with which pre-analytical variables are identified by personnel working in the coagulation laboratory was not previously examined. Training workshops offered in past studies focussed primarily on non-laboratory personnel involved in specimen collection, handling and transport during the pre-analytical phase [ 24 – 26 ]. These studies identified the impact of such training by determining sample rejection rates before and after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the accuracy with which pre-analytical variables are identified by personnel working in the coagulation laboratory was not previously examined. Training workshops offered in past studies focussed primarily on non-laboratory personnel involved in specimen collection, handling and transport during the pre-analytical phase [ 24 – 26 ]. These studies identified the impact of such training by determining sample rejection rates before and after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Beş yüz doksan bir reddedilen numunenin 422'sinin hemoliz nedeni ile gerçekleşmesi kan alımı ile ilgili bir sorunun varlığını bize göstermektedir. Yapılan bu analiz sonucunda, kan alımı ile ilgili eğitimin ilgili sağlık personeline verilmesi, teknik hataların giderilmesi ve eğitimlerin sürdürebilirliğin sağlanması gerekmektedir (10) .…”
Section: Discussionunclassified
“…Yine Avcı ve ark. (10) preanalitik evreye yönelik aile hekimleri ve kan alma elemanlarına verdikleri eğitim sonucunda hataların giderek azaldığını kalite indikatörleri başlığı altında ortaya koymuşlardır.…”
Section: Hastane Bölümlerine Göreunclassified
See 1 more Smart Citation
“…In addition, the physician, health personnel (nurse, laboratory technician staff ), secretary, trainee student, and transport staff regularly receive training in laboratory processes, blood collection, and sample transport once a year. Studies in the literature have demonstrated the preliminary effects of continuing education on laboratory errors [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%